FUNGSI MANAJERIAL KEPALA SEKOLAH DALAM MEWUJUDKAN PROGRAM KEAGAMAAN DI SMA NEGERI TERAWAS - Muhammad Ali (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2015)
This study was motivated by the problems that exist in the SMA Terawas, namely; First, that educational success is only measured by the excellence of cognitive and barely measure affective and psychomotor domains, thus fostering character and moral neglect. Secondly, the shortage of school hours is just 2x45 minutes/week for Islamic Religious Education provided in schools. The shortage of teaching hours is certainly not going to be able to attain moral guidance. Facing upheavals, the school principal in completing this task to occupy the position of manager, which regulates the management in solving complex problems, then the necessary managerial functions principals who have a strategic function in determining the change through policies that become the authority of his duties, especially in realizing the program religious. Therefore, the focus of the problem in this thesis are (1) how the planning function principals in realizing religious program in SMA Terawas. (2) How the function of organizing principals in realizing the religious program in SMA Terawas. (3) How the function of the principal driving force in realizing the religious programs in SMA Terawas. (4) Any religious programs that have been realized in SMA Terawas through the managerial functions of the principal. (5) What are the barriers to exercising their religious program in SMA Terawas? This study uses a descriptive qualitative approach, the data collection tool in the form of observations, interviews, and documentation. Source of data used are primary and secondary. While data analysis using descriptive analysis Miles and Haberman interactive concept through triangulation. The analysis in this study revealed that: (1) In the institutional principals have done a managerial role as a figure who has always supported activities, exposing every activity, and the role of entrepreneurs in developing religious programs through a breakthrough and a big idea. The school principal also has to optimize the managerial functions through planning designed together with the overall school program, organizing the whole of existing resources, and the ability of the principal to motivate subordinates, as well as cooperating with various parties in realizing religious programs. (2) The religious program has been running well it is characterized by SMA Terawas pioneering in the use of Islamic dress (hijab) become compulsory clothing in the school environment. Likewise, infaq program is the forerunner to the construction of mosques in the school environment that makes SMA Terawas as the only public school that has a mosque in Musi Rawas. (3) The realization of religious programs in the SMA Terawas, a serious effort is jointly and positive support from all components in the school. (4) There is still limited awareness of some students of the importance of fostering the values of faith and piety become a bottleneck implementation of religious programs in SMA Terawas. With these results, it is suggested for further research to conduct research about realizing a religious program at the school through the managerial skills of principals.